DESIGNING CONVENTION AND EXHIBITION CENTER WITH GREEN ARCHITECTURE APPROACH IN MEDAN CITY - Febriansyah, Febriansyah; Abdillah , Wahyu (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The convention and exhibition center is a place to conduct MICE (Meeting, Incentive, Conference, and Exhibition) activities where the activities carried out are activities such as state conference meetings, meetings, art exhibitions, product exhibitions, concerts, and other events [1]. In the city of Medan, the facilities are still very limited along with the increase in population and the increasing need for meeting rooms and exhibition rooms, so the "Convention and Exhibition Center" was designed. The plan of this building is located on the street. H. Adam Malik, West Medan District, Medan City, North Sumatra.There are several problems in the West Medan area, namely an untidy environment and a lack of greenery in the area. Therefore, the application of Green Architecture was chosen to have a positive impact on residents and the surrounding environment by applying applicable principles. By carrying out several methods and design steps, this will present solutions to functional needs and green architecture solutions that answer design problems.